2008
DOI: 10.1002/app.28117
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of biodegradable chitosan and methoxy poly(ethylene glycol)‐b‐poly (ε‐caprolactone) blend homogeneous films

Abstract: Blend homogeneous films of chitosan and water-soluble methoxy poly(ethylene glycol)-b-poly(e-caprolactone) (MPEG-b-PCL) diblock copolymer with different blend ratios were prepared by aqueous solution blending method. The water-soluble MPEG-b-PCL was synthesized using MPEG with molecular weight of 5000 g/mol and stannous octoate as the initiating system. The molecular weight of MPEG-b-PCL obtained from 1 H-NMR was 5800 g/mol. FTIR spectra of the blend films showed that there were intermolecular bonds between ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
1
2
2
Order By: Relevance
“…The presence earlier [52]. It was also reported that by increasing the CHT wt%, the intensity of the characteristic peak of PCL should decrease as the conjugation with PCL and CHT chains suppresses the crystallization of PCL [31,[53][54][55]. Unlike the other reported data, in our case, this effect was not observed and we found a considerable increase of intensity of the PCL specific peak in the blend by increasing CHT wt.%.…”
Section: Microscopic Pcl/cht Chemical Structurecontrasting
confidence: 73%
“…The presence earlier [52]. It was also reported that by increasing the CHT wt%, the intensity of the characteristic peak of PCL should decrease as the conjugation with PCL and CHT chains suppresses the crystallization of PCL [31,[53][54][55]. Unlike the other reported data, in our case, this effect was not observed and we found a considerable increase of intensity of the PCL specific peak in the blend by increasing CHT wt.%.…”
Section: Microscopic Pcl/cht Chemical Structurecontrasting
confidence: 73%
“…These peaks of mass loss was observed in the derivative curves of CHI and mPEG-PCL (Figure 5). According to Niamsa et al, (2008) the peak mass loss for mPEG was found at 418ºC and the degradation of PCL was observed at 360ºC, coinciding with the temperature range of mass loss observed for the membranes containing mPEG-PCL 10 .…”
Section: Thermogravimetric (Tg) and Thermogravimetric Analysis (Dtg)supporting
confidence: 71%
“…One way to blend hydrophilic and hydrophobic molecules is to add chemicals that have both hydrophilic and hydrophobic moieties, such as surfactants 10 . Another alternative is to chemically modify the polymeric backbone to attach hydrophilic/hydrophobic molecules in order improve the compatibility.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, in most of the cases, it was reported that by increasing the weight fraction of CHT the intensity of the characteristic peak of PCL should decrease. It is stated that the conjugation with PCL and CHT chains suppresses the crystallization of PCL [99,[119][120][121]. Unlike the other reported data, in our case, this effect was not observed and we found a considerable increase of intensity of the PCL specific peak in the blend by decreasing PCL wt.% like the 29.5° peak which finally disappear for PCL/CHT 70/30.…”
Section: Crystalline and Thermal Propertiescontrasting
confidence: 86%